Ceramics and its Importance - Subedi, Mitra Mani (Himalayan Physics, 2013)
The term "ceramic" once referred only to clay-based materials. However, new generations of ceramic materials have tremendously expanded the scope and number of possible applications. Many of these new materials have a major impact on our daily lives and on our society. Ceramics has advanced far beyond its beginnings in clay pottery. Ceramic tiles cover the space shuttle as well as our kitchen floors. Ceramic electronic devices make possible high-tech instruments for everything from medicine to entertainment. Clearly, ceramics are our window to the future. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 80-82 Uploaded date: 12/23/2013